Benefits of Boredom: An 'Interlopers' Experience of Conducting Participant Observation on the Production Line. Issue 1 (24th January 2020) - Pass, Sarah
Abstract : Embracing a lyrical style of writing, the paper discusses the advantages of conducting participant observation and calls for its increased use in business and management research, especially the field of human resource management (HRM) . In a sector dominated by quantitative research methods, we are left with many unanswered questions about organisational life . While surveys have provided us with an abundance of 'hard' data, it has resulted in a lack of depth and understanding around the employee experience . Reflecting on a research project that explored the concept of high‐performance work systems (HPWS), the paper discusses a chance opportunity to undertake participant observation and how the experience not only changed the focus of the research project but provided a depth and understanding currently missing from the HRM/HPWS paradigm . Structured around 'lessons learnt', the paper calls for methodological eclecticism and hopes to encourage others to become 'interlopers' and embrace the benefits of conducting participant observation .